OLFML2A Downregulation Inhibits Glioma Proliferation Through Suppression of Wnt/β-Catenin Signaling - Ma, Shize; Duan, Lei; Dong, Huateng; Ma, Xiaodong; Guo, Xinyu; Liu, Jianli; Li, Guoqiang; Yu, Yue; Xu, Yanlong; Yuan, Guoqiang; Zhao, Xingkun; Tian, Guopeng; et al. (Frontiers in Oncology, 2021)
Glioma is a highly heterogeneous and lethal tumor with an extremely poor prognosis. Through analysis of TCGA data, we identified that OLFML2A is a key promotor of gliomagenesis. However, the molecular function of OLFML2A and its underlying mechanism of action in glioma remain unclear. In this study, we found that OLFML2A expression was significantly upregulated in glioma specimens and positively correlated with pathological grades in glioma patients. Moreover, Kaplan–Meier survival analysis of TCGA data revealed that glioma patients with higher OLFML2A expression had shorter overall survival. Importantly, OLFML2A knockdown in glioma cells inhibited cell proliferation and promoted apoptosis. Mechanistically, OLFML2A downregulation inhibits Wnt/β-catenin signaling by upregulating amyloid precursor protein (APP) expression and reducing stabilized β-catenin levels, leading to the repression of MYC, CD44, and CSKN2A2 expression. Furthermore, OLFML2A downregulation suppressed the growth of transplanted glioma subcutaneously and intracranially by inhibiting Wnt/β-catenin pathway-dependent cell proliferation. By uncovering the oncogenic effects in human and rodent gliomas, our data support OLFML2A as a potential therapeutic target for glioma.